SM22α Loss Contributes to Apoptosis of Vascular Smooth Muscle Cells via Macrophage-Derived circRasGEF1B. (16th March 2021) - Lv, Pin; Yin, Ya-Juan; Kong, Peng; Cao, Li; Xi, Hao; Wang, Ning; Yang, Hong-Chao; Lv, Yu-Hong; Chen, Ning; Wang, Rong; Dou, Yong-Qing; Wang, Hai-Yue; et al.
Abstract : Vascular smooth muscle cell (VSMC) apoptosis is a major defining feature of abdominal aortic aneurysm (AAA) and mainly caused by inflammatory cell infiltration. Smooth muscle (SM) 22 α prevents AAA formation through suppressing NF- κ B activation. However, the role of SM22 α in VSMC apoptosis is controversial. Here, we identified that SM22 α loss contributed to apoptosis of VSMCs via activation of macrophages. Firstly, deficiency of SM22 α enhanced the interaction of VSMCs with macrophages. Macrophages were retained and activated by Sm22α -/- VSMCs via upregulating VCAM-1 expression. The ratio of apoptosis was increased by 1.62-fold in VSMCs treated with the conditional media (CM) from activated RAW264.7 cells, compared to that of the control CM (P < 0.01 ), and apoptosis of Sm22α -/- VSMCs was higher than that of WT VSMCs (P < 0.001 ). Next, circRasGEF1B from activated macrophages was delivered into VSMCs promoting ZFP36 expression via stabilization of ZFP36 mRNA. Importantly, circRasGEF1B, as a scaffold, guided ZFP36 to preferentially bind to and decay Bcl-2 mRNA in a sequence-specific manner and triggered apoptosis of VSMCs, especially in Sm22α -/- VSMCs. These findings reveal a novel mechanism by which the circRasGEF1B-ZFP36 axis mediates macrophage-induced VSMC apoptosis via decay of Bcl-2 mRNA, whereas Sm22α -/- VSMCs have a higher sensitivity to apoptosis.